Analysis of Branch Office Efficiency in the Ranks of DKI Jakarta Regional Office BPJS Ketenagakerjaan - Kumalasari, Aristin Nanda; Nurhayati, Popong; Asnawi, Yudha Heriyawan (Asian Journal of Social and Humanities, 2025)
The number of active workers who register as BPJS Employment participants is still relatively low. This shows that the use of resources owned by branch offices has not been optimal in an effort to achieve the set targets. This study aims to analyze the efficiency of branch offices in the DKI Jakarta area using the Data Envelopment Analysis (DEA) method with a production approach, which is then followed by Tobit regression analysis to identify the factors that affect the efficiency level. The results of the study show that there is a variation in the level of efficiency between branch offices within the DKI Jakarta Regional Office during the period 2019 to 2023. During the five-year observation period, branch offices with a 3A classification were recorded to have the highest level of efficiency compared to other categories. Tobit's regression analysis revealed that the type of branch office had a significant negative effect on the level of efficiency. On the other hand, the variable in the number of claim cases actually shows a significant positive influence on efficiency. The formulation of recommendations based on the results of the analysis includes appreciation of best practices, adjustment of branch office types, digitization of JHT Claims, and management of employee mutation systems.